2019
DOI: 10.1016/j.ijmedinf.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect the use of electronic personal health records among patients: A systematic review

Abstract: ReuseThis article is distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs (CC BY-NC-ND) licence. This licence only allows you to download this work and share it with others as long as you credit the authors, but you can't change the article in any way or use it commercially. More information and the full terms of the licence here: https://creativecommons.org/licenses/ TakedownIf you consider content in White Rose Research Online to be in breach of UK law, please notify us by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
124
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(129 citation statements)
references
References 110 publications
(87 reference statements)
5
124
0
Order By: Relevance
“…To help implement our system into practice, we will perform further longitudinal acceptance modeling studies on the full version of our system to focus on the factors that affect older adults’ and health care professionals’ acceptance [ 70 ]. Following that, targeted strategies (eg, community-based technology support services and training workshops) will be promoted to improve user acceptance on our smart system.…”
Section: Discussionmentioning
confidence: 99%
“…To help implement our system into practice, we will perform further longitudinal acceptance modeling studies on the full version of our system to focus on the factors that affect older adults’ and health care professionals’ acceptance [ 70 ]. Following that, targeted strategies (eg, community-based technology support services and training workshops) will be promoted to improve user acceptance on our smart system.…”
Section: Discussionmentioning
confidence: 99%
“…Adoption of healthcare informatics generally and ePHR specifically from consumers perspective is a complicated process that has been identified by many factors (Najaftorkaman, 2016;Showell, 2017;Ozok et al, 2017;Abd-alrazaq et al, 2019a). In USA, a systematic review study was reviewing the factors affecting the adoption intention to use ePHR, around 59 factors related to intention to use PHR has been detected in the reviewed studies which shows how the study of this subject is very complex and affected by many variables, also the factors that affect the initial intention to use may be different from others that influence the continuity of use (Abd-alrazaq et al, 2019a).…”
Section: Factors Affecting Adoption Of Ephrmentioning
confidence: 99%
“…Despite the enormous benefits of ePHR systems but its adoption has been low in several countries including developing and developed countries (Ford et al, 2016;Katehakis et al, 2018), also its dispersion rate is slowly growing (Ford et al, 2016;Katehakis et al, 2018), many studies discussed several factors that can affect the adoption of using such systems and it was found that many factors can affect the adoption process (Abd-alrazaq et al, 2019a). these factors were either motivating or hindering the adoption process, knowing the true predictors of behavioral intention to use these systems is crucial for achieving success in making ePHR systems more usable and have a widespread in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying and understanding factors that affect patients’ use of ePHRs is crucial to develop interventions to increase patients’ adoption and improve the implementation success of ePHRs [17-22]. According to a systematic review conducted by Abd-alrazaq and colleagues [23], there are no published studies on factors affecting patients’ use of ePHRs in England. Although many studies have been conducted in other countries, they have several shortcomings, namely, (1) few studies were theory-based research [21,24-27], (2) many studies focused on factors that affect patients’ intention to use ePHRs instead of actual use [28-32], (3) many studies have assessed the factors that affect self-reported use rather than actual use [27,32-35], (4) almost all studies examined independent and dependent variables at one point in time using the same data collection instrument, so being at risk of common method bias [25,32,36], and (5) almost all studies did not differentiate between factors affecting initial use and continuing use of ePHRs.…”
Section: Introductionmentioning
confidence: 99%